The range of endometrial pathologies in patients with abnormal uterine bleeding at a tertiary care center in central India - Rabia Parveen Siddiqui; Varsha Pandey; Sonal Chandrakar; Vanita Bhaskar (MGM Journal of Medical Sciences)
Background: Endometrial disorders are among the most common gynecological conditions globally. Abnormal uterine bleeding (AUB) refers to any irregularity in the timing, volume, or pattern of menstrual blood flow. This study investigates the histopathological spectrum of endometrial changes across various age groups in patients presenting with AUB as their primary symptom.